Strategies to overcome nutritional and technological limitations of pulse proteins - Fatemeh Aghababaei; David Julian McClements; Milad Hadidi (Future Foods)
Shifting from animal- to plant-based proteins will be essential to address climate change, pollution, food insecurity, and biodiversity issues. Pulses are an abundant, affordable, and resilient agricultural crop that is rich in proteins. However, the application of pulse proteins in food products is often limited due to their poor functional, nutritional, and sensorial properties. This review article begins by highlighting the molecular characteristics of pulse proteins, including their composition and structure. It then discusses the limitations to their more widespread use in foods, including their low digestibility, the presence of anti-nutritional factors, the deficiency in some essential amino acids, their high allergenicity, the presence of off-flavors, and their restricted techno-functionality. The potential of several processing technologies to overcome these challenges are then assessed, including extrusion, fermentation, sonication, radiation, and enzymatic treatments. Previous research findings have demonstrated that many of these technologies can be used to enhance the functional, sensorial, and nutritional qualities of pulse proteins. Further development and application of these technologies may help to address the challenges currently holding back the more widespread application of pulse protein ingredients in foods.